GIS visualization of population censuses in Peninsular Malaysia: a case study of Jempol, Negeri Sembilan, 1947-2000 - Abd. Manan, Mohd Shahrudin; Hashim, Nor Rasidah (Universiti Putra Malaysia Press, 2010)
Census has become an important administrative tool for governments to trace and plan for national progress since it contains essential information about the populations. Studies of economics, sociology, history, rural development, and agriculture commonly used censuses. Nevertheless, these studies mostly focus on the textual and numerical analysis of the census data without paying much attention to the sense of space of the censuses. Hence, Geographic Information System (GIS) could help by enabling population censuses to be spatially visualized and analyzed. In this study, two common techniques in GIS were used to spatially visualize human population censuses of Jempol district, Negeri Sembilan in the 20th century. Using GIS, the available population census data of the district were transformed into choropleth and cartogram maps of population density. The two types of map were then compared based on their usefulness and appearance in visualizing the censuses. It was found that each type of maps has its own strengths and weaknesses, but overall, the application of GIS has been found to be an exciting and reliable medium for the spatial analysis and visualization of the censuses. The findings suggest that GIS adds another dimension in understanding past demographic phenomena in the study area. It is recommended that further research in this area, such as overlapping the spatial analysis with topographic elevations and socio-economic characteristics, as well as constructing linear and non-contiguous cartograms, should be conducted. Besides enhancing the spatial analysis of the censuses, this research paves way for the development of Historical GIS studies in Malaysia.